Copolymerzation of L,L-lactide with epsilon-caprolactone by using novel zinc L-proline organometallic catalyst - Pandey, Asutosh K. (E-Polymers, 2010)
Copolyesters based on L, L-lactide (LA) and e-caprolactone (CL) with different LA: epsilon-CL ratios were synthesized by ring opening polymerization using zinc (L-proline) as a catalyst. Ring opening polymerization results in random P(L, L-lactide-epsilon-caprolactone) copolymers of molecular weights between 9,800 to 30,000 and block copolymer up to 51,800 Da. H-1 NMR spectroscopy analysis was used for calculation of monomer incorporation in the copolymer. FT-IR spectra were used to differentiate between random and block copolymer using carbonyl region splitting. C-13 quantitative NMR spectroscopy analysis coupled with information from TGA and DSC allowed determination of the polymer structure. Copolymers (CP-1, CP-2 and CP-3) prepared by ROP are random copolymer (h > 1), while CP-4 prepared by ROP (sequential addition of epsilon-caprolactone and L, L-lactide) has a multi block character (h < 1). The LA number-average sequence length (L-LA) decreased from 14 to 5 for LA-CL 80:20 to 50:50 copolymers prepared by ROP. The copolymer (CP-4) prepared by sequential addition showed the number-average sequence length (L-LA) to be 83.0.